Късноантична и средновековна керамика от Седлари, Момчилградско - Katya Melamed; Emilia Evtimova (Приноси към българската археология, 2018)
The village of Sedlari is situated ca. 4 km to the west of the town of Momchilgrad in the Eastern Rhodope Mountains. The archaeological excavations on the terrace above the Varbitsa River, a tributary of Arda River, have been carried out for almost 35 years with several interruptions. The archaeological deposits reach ca. 3 m at some places. The multilayered site yielded a large amount of pottery dated back to the Early Byzantine and Medieval periods.